2013
DOI: 10.3109/14767058.2013.776535
|View full text |Cite
|
Sign up to set email alerts
|

Congenital malformations in infants conceived following assisted reproductive technology in comparison with spontaneously conceived infants

Abstract: Infants born following ART were at significantly increased risk for congenital malformations compared to live birth conceived spontaneously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 32 publications
0
20
0
5
Order By: Relevance
“…Of the 21 articles reviewed, 19 reported increased risk of birth defects, but only 13 had statistically significant results (Hansen et., 2002;Bonduelle et al, 2005;Sánchez-Albisua et al, 2007;Halliday et al, 2010;Davies et al, 2012;Källén et al, 2005;Belva et al, 2007;Fedder et al, 2013;Hansen et al, 2012;Klemetti et al, 2005;Farhi et al, 2013;Funke et al, 2010;Katalinic et al, 2004). Two studies reported that ICSI was not associated with increases in congenital malformations, but none were statistically significant (Sutcliffe et al, 2003;Place & Englert, 2003).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 21 articles reviewed, 19 reported increased risk of birth defects, but only 13 had statistically significant results (Hansen et., 2002;Bonduelle et al, 2005;Sánchez-Albisua et al, 2007;Halliday et al, 2010;Davies et al, 2012;Källén et al, 2005;Belva et al, 2007;Fedder et al, 2013;Hansen et al, 2012;Klemetti et al, 2005;Farhi et al, 2013;Funke et al, 2010;Katalinic et al, 2004). Two studies reported that ICSI was not associated with increases in congenital malformations, but none were statistically significant (Sutcliffe et al, 2003;Place & Englert, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…In most of the publications, the authors adjusted the data according to the variables that might have affected the outcomes: seventeen adjusted their data by maternal age (Hansen et al, 2002;Farhangniya et al, 2013;Bonduelle et al, 2005;Sanchez-Albisua et al, 2007;Halliday et al, 2010;Davies et al, 2012;Källén et al, 2005;Belva et al, 2007;Fedder et al, 2013;Ludwig et al, 2009;Ombele et al, 2005;Hansen et al, 2012;Klemetti et al, 2005;Farhi et al, 2013;Bonduelle et al, 2004;Katalinic et al, 2004;Knoester et al, 2008); seven for paternal age (Bonduelle et al, 2005;Davies et al, 2012;Ludwig et al, 2009;Place & Englert, 2003;Bonduelle et al, 2004;Katalinic et al, 2004;Knoester et al, 2008); ten for parity (Hansen et al, 2002;Halliday et al, 2010;Davies et al, 2012;Källén et al, 2005;Sutcliffe et al, 2001;Ombele et al, 2005;Hansen et al, 2012;Klemetti et al, 2005;Bonduelle et al, 2004;Knoester et al, 2008); seven for socio-economic level (Davies et al, 2012;Belva et al, 2007;Ludwig et al, 2009;Sutcliffe et al, 2001;Place & Englert, 2003;Klemetti et al, 2005;…”
Section: Resultsmentioning
confidence: 99%
“…Naturally conceived human embryos are produced by fusion of sperm and egg in a woman's reproductive tract, a process that can be replicated, although imperfectly [185][186][187], by in vitro fertilization. Recent work has shown that human embryos capable of surviving to the blastocyst stage can be produced by cloning [188].…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12] Kimi araştırmacılar YÜT çoğul gebeliklerinin spontan gebeliklerden perinatal özellik-ler açısından bir fark içermediğini iddia ederken, kimi araştırmacılar da YÜT çoğul gebeliklerinin ekstra risk taşıdığını ileri sürmüşlerdir. [9][10][11][12] Risk olarak belirtilen durumlar doğumsal malformasyon, preterm doğum, iri doğum ağırlığı ve sezaryen ile doğum olarak sırala-nabilir. [9][10][11] Biz de çalışmamızda YÜT ile elde edilen ço-ğul gebelikler ile spontan çoğul gebeliklerin perinatal akıbetlerini karşılaştırmayı amaçladık.…”
Section: Introductionunclassified
“…[9][10][11][12] Risk olarak belirtilen durumlar doğumsal malformasyon, preterm doğum, iri doğum ağırlığı ve sezaryen ile doğum olarak sırala-nabilir. [9][10][11] Biz de çalışmamızda YÜT ile elde edilen ço-ğul gebelikler ile spontan çoğul gebeliklerin perinatal akıbetlerini karşılaştırmayı amaçladık. Spontan ve YÜT çoğul gebeliklerinin perinatal akıbet karşılaştırmaları Tablo 3'te sunuldu.…”
Section: Introductionunclassified